2017
DOI: 10.1159/000484088
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Development of Aberrant Smooth Muscle Cell Phenotype in Abdominal Aortic Aneurysm Disease

Abstract: Abdominal aortic aneurysm (AAA) is a silent, progressive disease with a high mortality and an increasing prevalence with aging. Smooth muscle cell (SMC) dysfunction contributes to gradual dilatation and eventual rupture of the aorta. Here we studied phenotypic characteristics in SMC cultured from end-stage human AAA (≥5 cm) and cells cultured from a porcine carotid artery (PCA) model of early and end-stage aneurysm. Human AAA-SMC presented a secretory phenotype and expressed elevated levels of the differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 38 publications
(78 reference statements)
3
39
0
Order By: Relevance
“…Phenotypic ‘switching’ of aortic constituent cells contributes to aneurysm formation in abdominal, descending thoracic and aortic root aneurysms . This study confirms the simultaneous enhancement of both contractile and synthetic gene sets in MFS proposed by Crosas‐Molist et al who similarly observed an overexpression of both contractile markers and collagen I in human MFS specimens.…”
Section: Discussionsupporting
confidence: 89%
“…Phenotypic ‘switching’ of aortic constituent cells contributes to aneurysm formation in abdominal, descending thoracic and aortic root aneurysms . This study confirms the simultaneous enhancement of both contractile and synthetic gene sets in MFS proposed by Crosas‐Molist et al who similarly observed an overexpression of both contractile markers and collagen I in human MFS specimens.…”
Section: Discussionsupporting
confidence: 89%
“…However, T2DM-SMC cells were unequivocally distinct from ND cells, lending weight to the idea that additional mechanisms conferring accelerated aging and senescence in T2DM may be responsible. In support of this hypothesis, we recently demonstrated in cultured human SMC of both aortic and venous origin, that miRNA-145 expression levels did not correlate with chronological age but were elevated in abdominal aortic aneurysm SMC; a disorder associated with accelerated vascular aging (19).…”
Section: Discussionmentioning
confidence: 86%
“…SMC cultured on glass coverslips were fixed in 4% PFA prior to immunostaining with phosphohistone H2AX (H2AX) antibody (Cell Signaling Technologies #2577) as described previously (19). Coverslips were mounted using Prolong Gold antifade reagent containing DAPI (Thermo-Fisher Scientific) and imaged on a Zeiss 700 confocal microscope.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Phenotype transformation of vascular smooth muscle cells (VSMC) is considered a driving force of many vascular diseases, including aortic aneurysms (Bennett et al, 2016;Hortells et al, 2018;Riches et al, 2018). Human abdominal aortic aneurysm (AAA) is an age-related disease, de ned by dilation of the aorta by more than half of the original diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Today, VSMC phenotypic switching and calci cation are considered key in AAA formation (Petsophonsakul et al, 2019;Riches et al, 2018) and the phenotypic modulation has been shown to be an early event in the aorta before aneurysm growth (Ailawadi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%